[3 + 2] Cycloaddition with photogenerated azomethine ylides in β-cyclodextrin - Sohora, Margareta; Mandić, Leo; Basarić, Nikola (Beilstein Journal of Organic Chemistry, 2020)
Stability constants for the inclusion complexes of cyclohexylphthalimide 2 and adamantylphthalimide 3 with β-cyclodextrin (β-CD) were determined by 1H NMR titration, K = 190 ± 50 M−1, and K = 2600 ± 600 M−1, respectively. Photochemical reactivity of the inclusion complexes 2@β-CD and 3@β-CD was investigated, and we found out that β-CD does not affect the decarboxylation efficiency, while it affects the subsequent photochemical H-abstraction, resulting in different product distribution upon irradiation in the presence of β-CD. The formation of ternary complexes with acrylonitrile (AN) and 2@β-CD or 3@β-CD was also essayed by 1H NMR. Although the formation of such complexes was suggested, stability constants could not be determined. Irradiation of 2@β-CD in the presence of AN in aqueous solution where cycloadduct 7 was formed highly suggests that decarboxylation and [3 + 2] cycloaddition take place in the ternary complex, whereas such a reactivity from bulky adamantane 3 is less likely. This proof of principle that decarboxylation and cycloaddition can be performed in the β-CD cavity has a significant importance for the design of new supramolecular systems for the control of photoreactivity.
Keywords: [3 + 2] cycloadditions; β-cyclodextrin; inclusion complexes; photochemistry; phthalimides

Cycloaddition Reactions in Organic Synthesis - Kobayashi, S.; Jørgensen, K. A. (WILEY-VCH, 2002)

(untitled) - Chiacchio, U.; Padwa, A.; Romeo, G. (Curr. Org. Chem., 2009)

(untitled) - Hashimoto, T.; Maruoka, K. (Chem. Rev., 2015)

(untitled) - Martina, K.; Tagliapietra, S.; Veselov, V. V.; Cravotto, G. (Front. Chem. (Lausanne, Switz.), 2019)

(untitled) - Nájera, C.; Sansano, J. M. (Curr. Org. Chem., 2003)

(untitled) - Hladíková, V.; Váňa, J.; Hanusek, J. (Beilstein J. Org. Chem., 2018)

(untitled) - Ryan, J. H. (ARKIVOC, 2015)

(untitled) - Coldham, I.; Hufton, R. (Chem. Rev., 2005)

(untitled) - Yoon, U. C.; Kim, D. U.; Lee, C. W.; Choi, Y. S.; Lee, Y.-J.; Ammon, H. L.; Mariano, P. S. (J. Am. Chem. Soc., 1995)

(untitled) - Yoon, U. C.; Cho, S. J.; Lee, Y.-J.; Mancheno, M. J.; Mariano, P. S. (J. Org. Chem., 1995)

(untitled) - Griesbeck, A. G.; Hoffmann, N.; Warzecha, K.-D. (Acc. Chem. Res., 2007)

(untitled) - Kanaoka, Y. (Acc. Chem. Res., 1978)

(untitled) - Horvat, M.; Mlinarić-Majerski, K.; Basarić, N. (Croat. Chem. Acta, 2010)

(untitled) - Basarić, N.; Horvat, M.; Mlinarić-Majerski, K.; Zimmermann, E.; Neudörfl, J.; Griesbeck, A. G. (Org. Lett., 2008)

(untitled) - Horvat, M.; Görner, H.; Warzecha, K.-D.; Neudörfl, J.; Griesbeck, A. G.; Mlinarić-Majerski, K.; Basarić, N. (J. Org. Chem., 2009)

(untitled) - Cindro, N.; Halasz, I.; Mlinarić-Majerski, K.; Basarić, N. (Eur. J. Org. Chem., 2013)

(untitled) - Mandić, L.; Mlinarić-Majerski, K.; Griesbeck, A. G.; Basarić, N. (Eur. J. Org. Chem., 2016)

(untitled) - Sohora, M.; Šumanovac Ramljak, T.; Mlinarić-Majerski, K.; Basarić, N. (Croat. Chem. Acta, 2014)

(untitled) - Horvat, M.; Mlinarić-Majerski, K.; Griesbeck, A. G.; Basarić, N. (Photochem. Photobiol. Sci., 2011)

(untitled) - Šumanovac Ramljak, T.; Sohora, M.; Antol, I.; Kontrec, D.; Basarić, N.; Mlinarić-Majerski, K. (Tetrahedron Lett., 2014)

(untitled) - Sohora, M.; Vazdar, M.; Sović, I.; Mlinarić-Majerski, K.; Basarić, N. (J. Org. Chem., 2018)

(untitled) - Boscá, F.; Miranda, M. A. (J. Photochem. Photobiol., B, 1998)

(untitled) - Boscá, F.; Marín, M.-L.; Miranda, M. A. (Photochem. Photobiol., 2001)

Handbook of Organic Photochemistry and Photobiology - Boscá, F.; Marín, M.-L.; Miranda, M. A. (CRC Press, 2004)

(untitled) - Monti, S.; Sortino, S.; De Guidi, G.; Marconi, G. (J. Chem. Soc., Faraday Trans., 1997)

(untitled) - Martínez, L. J.; Scaiano, J. C. (J. Am. Chem. Soc., 1997)

(untitled) - Cosa, G.; Martínez, L. J.; Scaiano, J. C. (Phys. Chem. Chem. Phys., 1999)

(untitled) - Laferrière, M.; Sanramé, C. N.; Scaiano, J. C. (Org. Lett., 2004)

(untitled) - Blake, J. A.; Gagnon, E.; Lukeman, M.; Scaiano, J. C. (Org. Lett., 2006)

(untitled) - Chuang, Y. P.; Xue, J.; Du, Y.; Li, M.; An, H.-Y.; Phillips, D. L. (J. Phys. Chem. B, 2009)

(untitled) - Li, M.-D.; Du, Y.; Chuang, Y. P.; Xue, J.; Phillips, D. L. (Phys. Chem. Chem. Phys., 2010)

(untitled) - Xu, Y.; Chen, X.; Fang, W.-H.; Phillips, D. L. (Org. Lett., 2011)

(untitled) - Li, M.-D.; Yeung, C. S.; Guan, X.; Ma, J.; Li, W.; Ma, C.; Phillips, D. L. (Chem. – Eur. J., 2011)

(untitled) - Li, M.-D.; Su, T.; Ma, J.; Liu, M.; Liu, H.; Li, X.; Phillips, D. L. (Chem. – Eur. J., 2013)

(untitled) - Boscá, F.; Miranda, M. A.; Carganico, G.; Mauleón, D. (Photochem. Photobiol., 1994)

Supramolecular Photochemistry - Ramamurthy, V.; Inoue, Y. (Wiley, 2011)

(untitled) - Ramamurthy, V.; Sivaguru, J. (Chem. Rev., 2016)

(untitled) - Aoyama, H.; Miyazaki, K.-I.; Sakamoto, M.; Omote, Y. (Tetrahedron, 1987)

(untitled) - Koodanjeri, S.; Joy, A.; Ramamurthy, V. (Tetrahedron, 2000)

(untitled) - Shailaja, J.; Karthikeyan, S.; Ramamurthy, V. (Tetrahedron Lett., 2002)

(untitled) - Vízvárdi, K.; Desmet, K.; Luyten, I.; Sandra, P.; Hoornaert, G.; Van der Eycken, E. (Org. Lett., 2001)

(untitled) - Inoue, Y.; Dong, F.; Yamamoto, K.; Tong, L.-H.; Tsuneishi, H.; Hakushi, T.; Tai, A. (J. Am. Chem. Soc., 1995)

(untitled) - Inoue, Y.; Wada, T.; Sugahara, N.; Yamamoto, K.; Kimura, K.; Tong, L.-H.; Gao, X.-M.; Hou, Z.-J.; Liu, Y. (J. Org. Chem., 2000)

(untitled) - Fukuhara, G.; Mori, T.; Wada, T.; Inoue, Y. (Chem. Commun., 2005)

(untitled) - Fukuhara, G.; Mori, T.; Wada, T.; Inoue, Y. (J. Org. Chem., 2006)

(untitled) - Lu, R.; Yang, C.; Cao, Y.; Wang, Z.; Wada, T.; Jiao, W.; Mori, T.; Inoue, Y. (Chem. Commun., 2008)

(untitled) - Lu, R.; Yang, C.; Cao, Y.; Tong, L.; Jiao, W.; Wada, T.; Wang, Z.; Mori, T.; Inoue, Y. (J. Org. Chem., 2008)

(untitled) - Uekama, K.; Hirayama, F.; Irie, T. (Chem. Rev., 1998)

(untitled) - Takahashi, Y.; Miyashi, T.; Yoon, U. C.; Oh, S. W.; Mancheno, M.; Su, Z.; Falvey, D. F.; Mariano, P. S. (J. Am. Chem. Soc., 1999)

(untitled) - Wintgens, V.; Amiel, C. (J. Photochem. Photobiol., A, 2004)

(untitled) - Hynes, M. J. (J. Chem. Soc., Dalton Trans., 1993)

(untitled) - Rekharsky, M. V.; Inoue, Y. (Chem. Rev., 1998)

(untitled) - Worlikar, S. A.; Larock, R. C. (J. Org. Chem., 2008)

(untitled) - Basarić, N.; Horvat, M.; Franković, O.; Mlinarić-Majerski, K.; Neudörfl, J.; Griesbeck, A. G. (Tetrahedron, 2009)